2018
DOI: 10.1016/j.cardfail.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital and Three-Year Outcomes of Heart Failure Patients in South India: The Trivandrum Heart Failure Registry

Abstract: Participants with HF in the THFR have high 3-year all-cause mortality. Targeted hospital-based quality improvement initiatives are needed to improve survival during and after hospitalization for HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…There is very little available data about Acute Heart Failure in India like The Trivandrum Heart Failure Registry. 7 When Indian data was compared with western studies like ADHERE, OPTIMIZE, it was shown that there are many differences in the way of presentation to risk factors of mortality to response to treatment. 8,9 In ADHERE and OPTIMIZE, 52% of study population were females and 48% were males compared to Trivandrum registry showing 31% females and 69% males.…”
Section: Discussionmentioning
confidence: 99%
“…There is very little available data about Acute Heart Failure in India like The Trivandrum Heart Failure Registry. 7 When Indian data was compared with western studies like ADHERE, OPTIMIZE, it was shown that there are many differences in the way of presentation to risk factors of mortality to response to treatment. 8,9 In ADHERE and OPTIMIZE, 52% of study population were females and 48% were males compared to Trivandrum registry showing 31% females and 69% males.…”
Section: Discussionmentioning
confidence: 99%
“…In Kerala, CVD is the leading cause of death 4 , and HF is a major contributor to CVD mortality. Further, data from clinical registries from Kerala indicate that almost one in two patients die within a three-year period from the date of their original admission to a health care facility for HF 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Trivandrum Heart Failure Registry in India demonstrated a higher 3-year all-cause mortality (44.8%) in patients hospitalized for HF with higher incidence for patients with HF with reduced ejection fraction (HFrEF) (46.2%) compared to HF with preserved EF (40.8%). 3 …”
Section: Introductionmentioning
confidence: 99%